2023
DOI: 10.3389/fbioe.2023.1249753
|View full text |Cite|
|
Sign up to set email alerts
|

Challenge of material haemocompatibility for microfluidic blood-contacting applications

Gwenyth Newman,
Audrey Leclerc,
William Arditi
et al.

Abstract: Biological applications of microfluidics technology is beginning to expand beyond the original focus of diagnostics, analytics and organ-on-chip devices. There is a growing interest in the development of microfluidic devices for therapeutic treatments, such as extra-corporeal haemodialysis and oxygenation. However, the great potential in this area comes with great challenges. Haemocompatibility of materials has long been a concern for blood-contacting medical devices, and microfluidic devices are no exception.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 228 publications
(286 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that the protein adsorption specificity and selectivity of materials have an important impact on the blood compatibility of materials [ 38 ]. It is generally believed that the albumin adheres to the surface of the materials can cause the formation of biological passivation film on the material surface, and inhibit the adhesion of platelets, thus preventing thrombosis [ 39 , 40 ]. Adhesion of fibrinogen can activate and accelerate platelet adhesion and coagulation process [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the protein adsorption specificity and selectivity of materials have an important impact on the blood compatibility of materials [ 38 ]. It is generally believed that the albumin adheres to the surface of the materials can cause the formation of biological passivation film on the material surface, and inhibit the adhesion of platelets, thus preventing thrombosis [ 39 , 40 ]. Adhesion of fibrinogen can activate and accelerate platelet adhesion and coagulation process [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…2) An optimized vascular network coupled with effective surface modifications and coatings to minimize the foreign body response of the device. 241 The functions of the heart and arteries are mechanical rather than chemical, thus an effort to recreate in the systems the forces and stresses produced by the blood flow on the walls of the cardiovascular vessels is mandatory. The blood flow path should reproduce the circular vascular channel geometry, follow natural scaling and branching laws, and exhibit velocities and shear stress in a physiological range.…”
Section: Discussionmentioning
confidence: 99%
“…From the earlier coatings of simple antifouling fluorocarbons [56], plasma deposition has now evolved to embrace more complex Zwitterionic antifouling layers [57]. Bio-compatible layers can now be prepared from materials such as organosilicons [55], and plasma processing is a key step in the manufacture of blood-compatible coatings [58]. The development of barrier coatings for a range of medical and non-medical applications is a growing area [59].…”
Section: Deposition Of Biocompatible and Adhesive Coatingsmentioning
confidence: 99%